Accurate outdoor positioning - Seng, Kerwin Wei Shen (Nanyang Technological University, 2021)
The advancement of wireless technology has improved our quality of life. Such wireless technology has made areas like communication and localization convenient and accessible. For instance, Global Positioning System (GPS) has made locating a user’s position easily accessible to anyone. The main setback of using the GPS is that it would not be able to operate in areas with poor reception and without a direct line of sight to the satellite. Such areas include urban areas with high-rise buildings and subways. The aim of this project is to study the feasibility of using RSSI signals for outdoor positioning in areas with poor GPS reception. An RSSI path loss model is created after collecting RSSI and positioning data, during the experiment phase, to improve our understanding of the RSSI and distance relationship. The results obtained show that using RSSI for positioning yields good positioning estimates.